2018
DOI: 10.24820/ark.5550190.p010.404
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of dihydropyranones and dihydropyrano[2,3-d][1,3]dioxine-diones by cyclization reaction of Meldrum’s acid with arylaldehydes and 1,3-dicarbonyls under thermal and ultrasound irradiation

Abstract: The present paper deals with the synthesis of novel dihydropyranone and dihydropyrano [2,3-d][1,3]dioxinedione derivatives via one-pot three-component reaction between Meldrum's acid, arylaldehydes, and various 1,3-dicarbonyls in the presence of KOH as a base in H2O:EtOH under thermal and ultrasound irradiation. It was observed that ultrasound-assisted method gave 80-94% yields in 30-45 min as against 120-280 min required to get 60-82% yields by thermal method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Similarly, ultrasound‐promoted synthesis utilizes an environment friendly source of energy, i. e., ultrasonic radiation [112] . And it is commonly known as sonochemistry which has served as a method feasible for the synthesis of various compounds such as 3‐(5,6‐dihydropyrazinyliden)‐1 H ‐indol‐2‐ones, [113a] dihydropyranone, dihydropyrano[2,3‐ d ][1,3]dioxinedione derivatives, [113b] and linked bis‐heterocycle peptidomimetics, [113c] 3‐selanylindoles [113d] and selenium‐containing chrysin derivatives [113e] …”
Section: Overview On Selenium‐catalyzed/selenium Incorporating Transfmentioning
confidence: 99%
“…Similarly, ultrasound‐promoted synthesis utilizes an environment friendly source of energy, i. e., ultrasonic radiation [112] . And it is commonly known as sonochemistry which has served as a method feasible for the synthesis of various compounds such as 3‐(5,6‐dihydropyrazinyliden)‐1 H ‐indol‐2‐ones, [113a] dihydropyranone, dihydropyrano[2,3‐ d ][1,3]dioxinedione derivatives, [113b] and linked bis‐heterocycle peptidomimetics, [113c] 3‐selanylindoles [113d] and selenium‐containing chrysin derivatives [113e] …”
Section: Overview On Selenium‐catalyzed/selenium Incorporating Transfmentioning
confidence: 99%
“…7 In view of the importance of bicyclic -lactones, tremendous efforts have been made in the past two decades. [8][9][10][11][12] For instance, Shi et al demonstrated that chiral thiourea−tertiary amine can catalyze [3 + 3] cyclization of 4-arylidene-2-aryloxazol-5(4H)-ones with cyclohexane-1,3-diones for the synthesis of bicyclic -lactones. 13 In 2018, a bifunctional organocatalyst-catalyzed cascade reaction for the access to bicyclic -lactones involving -unsaturated--ketophosphonates and cyclic 1,3-dicarbonyls has been nicely described by Albrecht and co-workers.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29][30] No doubt, all the existing methods are useful and effective, but have significant limitations such as, the use of an expensive catalyst, a special apparatus, low yields, difficult work-up, or a multistep synthetic sequence. In continuation of our attempts to develop novel synthetic routes for the preparation of oxygen-containing organic compounds, using multicomponent approaches, [31][32][33][34] we describe herein a simple and efficient approach for the synthesis naphtho[2,1-b]furans 4 through an one-pot three-component reaction of Meldrum's acid 1, arylglyoxal 2, and a β-naphthol 3 in a two-stage processes.…”
Section: Introductionmentioning
confidence: 99%